First report of Asian pistachio rust (Pileolaria pistaciae) in Pakistan. Issue 2 (2nd April 2020) - Ishaq, Aamna; Aime, Mary C.; Ayala, Elena K.; Ullah, Sadiq; Afshan, Najam S.; Fahad, Muhammad; Fiaz, Muhammad; Niazi, Abdul R.; Khalid, Abdul N.
Abstract: Pileolaria pistaciae: is a species originally found attacking Pistacia chinensis Bunge in Japan and a few other Asian countries. In this study, we report the presence of P. pistaciae in Pakistan. Infected leaves of P. chinensis were collected from two different sampling sites in the Abbottabad and Shangla districts of Khyber Pakhtunkhwa province of Pakistan in September-October, 2014. The causal fungus was observed and identified based on combined results of morphological and molecular characterization of the internal transcribed spacer and large subunit regions of ribosomal DNA. This is the first report in Pakistan of Asian Pistachio rust disease caused by P. pistaciae .